2023
DOI: 10.21203/rs.3.rs-3238115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial evaluation of LncRNA A2M-AS1 gene expression in multiple sclerosis patients

Shaghayegh Mohammadi,
Mansoureh Azadeh,
Tahereh Saeghyian
et al.

Abstract: Introduction: Multiple sclerosis (MS) is one of the three leading neurodegenerative diseases worldwide. Genes expression profiles studies play important role in recognition and prevention of disease. Considering the inherent ability of biomarkers to diagnose and prognosis the occurrence of a disease, with the aim of gene therapy and changing gene expression, it can be helped to treat it. In this study, by examining the gene interaction and expression of non-coding gene in patients with multiple sclerosis, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated some potential non-coding biomarkers of diverse cancer types, including BC [44][45], GC [46], and also different immune-related diseases including multiple sclerosis [47].To gather new and reliable data and develop a sound experiment, we conducted a consistent bioinformatics analysis to identify a key gene involved in colorectal cancer (CRC) development and explore other biological factors that may influence gene expression and the progression of CRC. Through our initial bioinformatics analysis, we discovered two novel long non-coding RNAs (lncRNAs), LINC01132 and LINC02542, which showed significant downregulation in CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated some potential non-coding biomarkers of diverse cancer types, including BC [44][45], GC [46], and also different immune-related diseases including multiple sclerosis [47].To gather new and reliable data and develop a sound experiment, we conducted a consistent bioinformatics analysis to identify a key gene involved in colorectal cancer (CRC) development and explore other biological factors that may influence gene expression and the progression of CRC. Through our initial bioinformatics analysis, we discovered two novel long non-coding RNAs (lncRNAs), LINC01132 and LINC02542, which showed significant downregulation in CRC samples.…”
Section: Discussionmentioning
confidence: 99%